Association between having no sons and using no contraception among a nationally representative sample of young wives in Nepal. Issue 2 (7th March 2013) - Raj, Anita; Vilms, Rohan J.; McDougal, Lotus; Silverman, Jay G.
Abstract: Objective: To examine whether a lack of sons predicts non‐use of contraception among young wives in Nepal. Methods: Data were obtained from married females aged 15–24 years who participated in the Nepal 2011 Demographic and Health Survey (n = 2439). Multivariate models were used to test predictions of modern contraception use with the following variables: having no sons, social inequities (wealth, education, rural residence, and caste), gender inequities (early age at marriage, spousal age, and education gaps), respondent age, parity, and geographic region. Results: Most wives (79%) reported using no modern contraception. Non‐use was more likely among those with no living sons (adjusted odds ratio [AOR], 1.6; 95% confidence interval [CI], 1.2–2.2), and those who married as a minor (AOR, 1.4; 95% CI, 1.02–1.9) and/or resided in a rural area (AOR, 1.6; 95% CI, 1.3–2.5). Having no daughters was negatively associated with non‐use of contraception (AOR, 0.7; 95% CI, 0.5–0.9). Conclusion: Contraception use is not common among young wives in Nepal. It is, however, more likely among wives with sons and less likely among wives with daughters, demonstrating that son preference continues to affect contraception use among the next generation of mothers in Nepal.